2017
DOI: 10.1080/21645515.2017.1405882
|View full text |Cite
|
Sign up to set email alerts
|

Report from enhanced safety surveillance of two influenza vaccines (Vaxigrip and Intanza 15 μg) in two European countries during influenza season 2016/17 and comparison with 2015/16 season

Abstract: Passive enhanced safety surveillance (ESS) was implemented in the United Kingdom and in the Republic of Ireland for Vaxigrip and Intanza 15 µg influenza vaccines during the 2016/17 influenza season. Lessons learned during 2015/16 ESS implementation were integrated and applied towards the current ESS. The primary objective was to estimate the reporting rates of suspected adverse reactions (ARs) occurring within 7 days of vaccination with Vaxigrip or Intanza 15 µg. For Vaxigrip (N = 962), 17 vaccinees (1.8%) rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 6 publications
3
14
0
Order By: Relevance
“…Early influenza vaccine safety surveillance aims to identify potential new safety concerns as soon as possible, before the peak period of mass immunization. 2 As in previous EPSS studies, 8,9 no safety issues were observed during the NH 2017/ 18 influenza season in participants receiving IIV3-ID or IIV3. Similarly, for IIV4, the EPSS showed no difference between the reported rates of ARs and those expected based on clinical trial data.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Early influenza vaccine safety surveillance aims to identify potential new safety concerns as soon as possible, before the peak period of mass immunization. 2 As in previous EPSS studies, 8,9 no safety issues were observed during the NH 2017/ 18 influenza season in participants receiving IIV3-ID or IIV3. Similarly, for IIV4, the EPSS showed no difference between the reported rates of ARs and those expected based on clinical trial data.…”
Section: Discussionmentioning
confidence: 65%
“…ARs reported by each participant were collected using an Information Request Management System and were confirmed by a structured telephone interview as described previously. 8,9 All events reported spontaneously by participants or healthcare professionals were considered as suspected ARs (i.e., vaccinerelated) unless the participants specifically stated that they believed the events were unrelated or that a causal relationship could be excluded. No causality assessment was requested from the participants or healthcare professionals.…”
Section: Study Conduct and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides clinical trials, many commercial MN products have been developed for vaccination and are available nowadays. These commercial products, for example, Nanopatch TM [159], Fluzone Intradermal ® [160], and Intanza ® [161], have been published in journals, and contributed to public health against pestilence [162,163].…”
Section: Vaccine Deliverymentioning
confidence: 99%